Neonatal outcomes associated with antimicrobial resistance: A retrospective cross-sectional study - Prashant Chandra, Faiza Iqbal, Mazhuvancherry Kesavan Unnikrisnan, Purkayastha Jayashree, Padmaja A. Shenoy, Stanly Elstin Anburaj, Vilakkathala Rajesh,, Mallayasamy Surulivelrajan,, Leslie Edward Lewis (Journal of Applied Pharmaceutical Science, 2023)
Neonatal sepsis (NS) is a leading cause of morbidity and mortality requiring immediate admission and prolonged neonatal intensive care unit (NICU) stay. This study attempts to identify factors associated with NS and its outcomes. A total of 186 NS case records (January 2017 to September 2019) were analyzed retrospectively. Multiple logistic regression and linear regression were employed to determine the factors associated with mortality, length of NICU stay, and treatment cost with a significance level of p ≤ 0.05. The mean neonatal age was 6.8 ± 9.5 days. Culture reports identified Klebsiella pneumonia (69%) as the major pathogen. Forty-four percent of neonates died, of whom 57% and 44% suffered early-onset sepsis and late-onset sepsis respectively. Logistic regression showed that mortality was significantly associated with platelet count (OR = 0.998; 95% CI =0.996–1.000) and very low birth weight (LBW) (OR = 2.427; 95% CI = 1.103–5.342). Linear regression showed that the number of definitive antibiotics used was associated with prolonged length of NICU stay. Also, length of NICU stay, number of definitive antibiotics, seizures, and heart disease, were significantly associated with overall cost. Mortality was higher with early-onset of sepsis than with late-onset of sepsis. The study could help policymakers and clinical practitioners to develop and implement targeted interventions that potentially reduce the global prevalence of NS.